Anti-GluK2 Encephalitis in an Asian Child: A Case Report and Literature Review - Chen S; Kessi M; He F; Yin F; Peng J; Yang L (ImmunoTargets and Therapy)
Shimeng Chen,1 Miriam Kessi,1 Fang He,1– 3 Fei Yin,1– 3 Jing Peng,1– 3 Lifen Yang1– 3 1Department of Pediatrics, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2Hunan Intellectual and Developmental Disabilities Research Center, Pediatrics, Changsha, People’s Republic of China; 3Clinical Research Center for Children Neurodevelopmental Disabilities of Hunan Province, Xiangya Hospital, Central South University, Changsha, People’s Republic of ChinaCorrespondence: Lifen Yang, Department of Pediatrics, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of China, Tel +86 − 1367435745, Fax +86-731-84327332, Email yanglifen7@126.comBackground: Anti-glutamate kainate receptor subunit 2 (anti-GluK2) antibodies mediated encephalitis is very rare in both children and adults. This study aimed to describe the second report of the anti-GluK2 encephalitis worldwide, the first youngest patient worldwide, and the first case ever in Asia. Besides, this study provides a summary of the clinical manifestations of all previous reported cases.Methods: The patient was attended at the Department of Pediatrics, Xiangya Hospital, Central South University. Anti-GluK2 antibodies were tested in the serum and cerebrospinal fluid (CSF) by the indirect immunofluorescence on cell-based assays. The clinical information of the patient was collected. In addition, a literature search was carried out in the PubMed.Results: Our patient was a male who presented with lethargy, recurrent dizziness and vomiting, headache and cerebellar ataxia at the age of 13 years. Prodromal illnesses included Herpes Zoster infection and Mycoplasma pneumonia. The anti-GluK2 antibodies and elevated IL-6 levels were detected in serum while high oligoclonal bands levels were found in the CSF. The intravenous methylprednisolone, immunoglobulin, antibiotics and other symptomatic treatments helped the patient to recover full. We could only find one previous report in the literature (from Barcelona). The literature review plus our report unveiled eight patients with pure anti-GluK2 antibodies related encephalitis. The median age of onset was 28.50 years and majority were males (75.00%). Most of the cases (87.50%) presented with acute cerebellitis symptoms and signs. Preceding or concurrent infection was observed in two patients, while paraneoplastic tumors were observed in two patients. Patients had non-parenchymal brain lesions; the commonest anomalies were those localized in the cerebellum (62.50%).Conclusion: Our report provides more evidence that anti-GluK2 antibodies may be pathogenic for the autoimmune encephalitis (cerebellitis). Immunotherapy can be used to treat it with good outcome.Keywords: anti-glutamate kainate receptor subunit 2 (anti-GluK2) antibodies, encephalitis, cerebellitis, immunotherapy